Supersonic jet interactions with a micro-engineered skimmer. (15th May 2018) - Wright, S; Syms, R R A
Abstract: A micro-engineered, skimmer-based vacuum interface has been demonstrated and used to investigate gas dynamics on a sub-millimeter length scale. The interface is fabricated as a stacked assembly of silicon dies, based on an anisotropically etched inlet orifice and a pyramidal skimmer cone formed in electroplated nickel. Expansion of gas into vacuum, interaction of a supersonic jet with the skimmer and transmission of a collimated beam into a second vacuum stage have all been imaged with a schlieren microscope. Using a glass-walled vacuum chamber, flow patterns upstream and fully downstream of the skimmer have been imaged together for the first time. At low first-stage pressures, the 150–200 µ m tall skimmers cannot fully penetrate the shock arising from interaction of the jet with the back wall. However, as the pressure is increased, a multiple shock cell structure evolves, the jet narrows and transmission rises sharply. Eventually, a collimated beam is transmitted to the second stage. When the skimmer aperture is smaller than the source aperture, a series of distinct peaks is evident in a plot of transmission against first-stage pressure. Imaging shows that at each successive peak, the number of shock cells increases by one and the skimmer inlet is coincident with a node.